Wacana Otonomi Seksualitas Perempuan: Sisilism Menolak Standar Ganda - Putri Setia Ningsih (School of Communication Science and Media Business, 2022)
Sexuality is an entity that is fluid and socially defined over a particular space and time. As a discourse, power/knowledge relations basically define sexuality. This research aims to explain how Sisil conveys the discourse of female sexuality on her Sisilism YouTube channel. Sisil and her YouTube channel became the subject of this research, and her formal object is the discussion of female sexuality in Sisilism videos. This research has the purpose to understand how the discourse of sexuality became an arena of the struggle for the practice of power/knowledge. The videos discussing women's sexuality published from 2016- 2022 were selected as a collection of texts that were analyzed using the Critical Discourse Analysis method described by Norman Fairclough. Through text analysis, discursive practice, and social practice, this study explains that female sexuality is shaped and produced through the discourse of the autonomy of female sexuality. The discourse shows Sisil’s agency to reject the double standards of women's sexuality that exist in Indonesian society and she's embracing it by adopting postfeminist concepts of gender and sexuality as a signal of women's liberations. Keywords: female sexuality, Critical Discourse Analysis, resistance, autonomy, postfeminism